2021
DOI: 10.3390/pharmaceutics13111749
|View full text |Cite
|
Sign up to set email alerts
|

Formulation, Optimization and Evaluation of Luteolin-Loaded Topical Nanoparticulate Delivery System for the Skin Cancer

Abstract: In the present study, luteolin (LT)-loaded nanosized vesicles (LT-NVs) were prepared by a solvent evaporation–hydration method using phospholipid and edge activator. The formulation was optimized using three factors at a three-level Box–Behnken design. The formulated LT-NVs were prepared using the three independent variables phospholipid (A), edge activator (B) and sonication time (C). The effect of used variables was assessed on the vesicle size (Y1) and encapsulation efficiency (Y2). The selection of optimum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 52 publications
3
14
0
Order By: Relevance
“…In a study, Lu-loaded nanovesicles were further transformed into Carbopol 934 gel (LT-NV-optG). 120 Compared with pure Lu, LT-NV-optG displayed suitable viscosity, pH, coatability, and sustained release characteristics, leading to a 2fold enhancement in permeability. Additionally, LT-NV-optG demonstrated no skin irritation and exhibited an enhanced inhibitory effect on skin cancer cell lines.…”
Section: Novasomesmentioning
confidence: 99%
“…In a study, Lu-loaded nanovesicles were further transformed into Carbopol 934 gel (LT-NV-optG). 120 Compared with pure Lu, LT-NV-optG displayed suitable viscosity, pH, coatability, and sustained release characteristics, leading to a 2fold enhancement in permeability. Additionally, LT-NV-optG demonstrated no skin irritation and exhibited an enhanced inhibitory effect on skin cancer cell lines.…”
Section: Novasomesmentioning
confidence: 99%
“…Through several studies, it has been reported to have antioxidant activity in preventing/treating age-related diseases and oxidative stress such as neuronal and cardiovascular disorders , as well as cancer. , This is presumably because it contains chemical compounds such as quercetin (QU) , and luteolin (LU). , Due to their potential to contribute a hydrogen atom to the DPPH radical, these bioactive components demonstrated the synergistic impact of a high radical scavenging activity. However, there are a few limitations caused by the original nature, such as low solubility in water resulting in reduced skin permeation abilities. In addition, the stratum corneum, which is the outermost layer of the skin, acts as a penetration barrier by blocking the delivery of active ingredients into the skin. This is important because the potential efficacy of QU and LU in preventing cell damage until necrosis mainly occurs in the epidermis. , Various approaches in terms of drug targeting and carrier systems with different routes of administration were studied to overcome these limitations and achieve more effective therapeutic efficacy. …”
Section: Introductionmentioning
confidence: 99%
“…With the different pH of the medium, the drug will be intelligently released. Imran Kazmi et al [ 23 ] studied the treatment of skin cancer with luteolin-loaded CBP hydrogel. Maimoona Qindeel et al [ 24 ] studied CBP hydrogel loaded with methotrexate for the treatment of rheumatoid arthritis.…”
Section: Introductionmentioning
confidence: 99%